Regulation of apoptosis through bcl-2/bax proteins expression and DNA damage by Zanthoxylum alatum. (3rd March 2016) - Karmakar, Indrajit; Haldar, Sagnik; Chakraborty, Mainak; Chaudhury, Keya; Dewanjee, Saikat; Haldar, Pallab Kanti
Abstract: Context : Many of the major chemotherapeutic agents are secondary metabolites found in nature. Zanthoxylum alatum Roxb. (Rutaceae) is traditionally used in the treatment of various diseases. Objective : The present study evaluates the apoptotic activity of methanol extract of Z. alatum (MEZA) on Ehrlich ascites tumor (EAT) in Swiss albino mice. Materials and methods : The presence of flavonoids in MEZA was standardized by HPLC. The in vitro cytotoxicity of MEZA was measured by the MTT assay. The in vivo antitumor activity of MEZA (100 and 200 mg/kg b.w., i.p. for 9 days) was also evaluated. On the 10th day, EAT tumor volume, cell viability, and hematological parameters were assayed. Apoptotic morphology was determined by acredine orange/ethedium bromide using fluorescence microscopy. Apoptosis percentage was measured by flow cytometric analysis using annexine-V-FITC. Also, DNA damage and bcl-2/bax were estimated by UV-method and western blot, respectively. Results and discussion : HPLC analysis revealed presence of three flavonoids, rutin, myricetin, and quercetin. MEZA showed satisfactory cytotoxicity in MTT assay (IC50 = 111.50 µg/ml). The extract significantly ( p < 0.01) changed the tumor volume, viable, non-viable cell count, and hematological parameters towards the normal. Apoptotic activity of MEZA was confirmed by acridine orange/ethidium bromide staining, annexin-V-FITC staining, DNA fragmentation, and Bcl-2/Bax ratio. Conclusion : The study showed that MEZA has antitumor activity which may be due to the presence of flavonoids in the extract.